THU0261 Pregnancy course and outcome in sle patients compared to patients with other connective tissue and inflammatory rheumatic diseases - data from a prospective cohort study. (15th June 2017) - Strangfeld, A; Bungartz, C; Weiß, A; Schneider, M; Richter, J; Zink, A; Fischer-Betz, R
Abstract : Background: Patients with systemic lupus erythematosus (SLE) are at increased risk for pregnancy complications and adverse pregnancy outcomes. During the past decades, advances in drug treatment and management during pregnancy made successful pregnancy in patients with SLE possible. Less is known about pregnancy course in other connective tissue diseases (OCTD). Objectives: To compare pregnancy courses and outcomes in SLE patients with those in OCTD patients and patients with other inflammatory rheumatic diseases. Methods: The German Rhekiss register is designed as nationwide, web-based longitudinal observational cohort study. Pregnant patients with confirmed diagnose of inflammatory rheumatic disease are eligible to be enrolled until the 20th week of pregnancy regardless of drug treatment. At baseline, sociodemographic parameters, prior pregnancies, comorbidities and antibody status are reported. During pregnancy, rheumatologists and patients report drug treatments, course of the maternal disease, development of fetus and complications once per trimester. After delivery, the pregnancy outcome and child development during the first two years of life are collected. Results: Until October 2016, data of 392 patients were available and grouped according to their disease in SLE patients, those with other connective tissue disease (OCTD) and patients with all other diagnoses (allO). 121 women had already completed their pregnancy with known outcome. Of them, most patients in the OCTD group were diagnosed with undifferentiated connective tissue disease (9), Sjögren Syndrome (5) and mixed connective tissue disease (5). The allO group included rheumatoid arthritis (28), psoriatic arthritis (10), spondyloarthritis (11), and JIA (8). The proportion of children born at term was lowest in patients with SLE (79%), compared to OCTD (91%) and allO patients (88%). The table shows selected baseline and outcome parameters. In early pregnancy, more patients with SLE reported low disease activity and a higher proportion was diagnosed by the rheumatologist as having mild disease than in the other diagnoses groups. During pregnancy, flares occurred rarely in SLE and OCTD patients, whereas a substantial proportion of patients in the allO group had multiple flares. However, serious complications during and after pregnancy occurred more often in SLE and OCTD patients, as well as congenital anomalies and complications. Due to the low number of events and completed pregnancies, associations to suspected risk factors couldn't be analyzed yet. Conclusions: Although most patients with SLE or OCTD had a favorable course and outcome of pregnancy, compared to patients with other inflammatory rheumatic diseases substantially more complications and adverse pregnancy outcomes occurred. The association to specific risk factors predicting adverse pregnancy outcomes could not yet be analyzed. At the time of the EULAR congress we expect at least twice as much completed pregnancies. All patients with SLE and OCTD should be tightly screened during pregnancy with timely and adequate adjustment of drug treatments. Acknowledgements: Rhekiss is a collaborative project of the DRFZ Berlin and the Rheumazentrum Rhein-Ruhr e.V. Düsseldorf, jointly funded by both institutions. Disclosure of Interest: None declared